Dexmedetomidine protects cells from Angiotensin II-induced smooth muscle cell phenotype switch and endothelial cell dysfunction. Issue 4 (16th February 2023) - Dai, Min; Zhu, Xiaohong; Zeng, Simin; Liu, Qiang; Hu, Ruilin; Huang, Lianghui; Wang, Yu; Deng, Jun; Yu, Qi
ABSTRACT: Abdominal aortic aneurysm (AAA) is a vascular disorder greatly threatening life of the elderly population. Dexmedetomidine (DEX), an α2-adrenergic receptor agonist, has been shown to suppress AAA development. Nevertheless, the signaling pathways that might be mediated by DEX in AAA has not been clarified. Vascular smooth muscle cells (VSMCs) and endothelial cells (ECs) were treated with Angiotensin II (Ang II) to mimic AAA in vitro . BrdU, wound healing, and Transwell assays were utilized for measuring VSMC proliferation and migration. Western blotting was used for evaluating protein levels of contractile VSMC markers, collagens and matrix metalloproteinases (MMPs) in VSMCs as well as apoptosis- and HMGB1/TLR4/NF-κB signaling-related markers in ECs. Cell adhesion molecule expression and monocyte-endothelial adhesion were assessed by immunofluorescence staining and adhesion assays. Flow cytometry was implemented for analyzing EC apoptosis. Hematoxylin-eosin staining and ELISA were used to detect the effect of DEX in vivo . In this study, DEX inhibited Ang II-evoked VSMC phenotype switch and extracellular matrix degradation. DEX suppressed the inflammatory response and apoptosis of ECs induced by Ang II. DEX inhibited HMGB1/TLR4/NF-κB signaling pathway in Ang II-treated ECs. DEX attenuated Ang II-induced AAA and inflammation in mice. Overall, DEX ameliorates Ang II-induced VSMC phenotype switch, and inactivates HMGB1/TLR4/NF-κB signaling pathway to alleviate Ang II-induced EC dysfunction.